Sugarcane interaction x harvest times in Pernambuco Center Microrregion by mixed models (Research, Society and Development, 2020)
The objective of this work was to verify the influence of harvest times on the maturation of sugarcane varieties and to identify those with higher agro-industrial productivity through the mixed model methodology. 26 commercial varieties were evaluated in three cycles and three harvest times, with the following traits being evaluated: tons of sucrose per hectare (TSH), tons of cane per hectare (TCH), percentage of sucrose in the sugarcane juice (PCC) and totals recoverable sugars (TRH). The experiments were installed in a randomized block design with 4 replications in a 3x3x26 factorial scheme. Two methodologies were used to analyze adaptability and stability: Huenh's non-parametric methodology and mixed linear models. The deviance analysis revealed significant differences between the varieties in the three harvest times, indicating that the respective harvest times are contrasting environments and influence the phenotypic expression of the traits. It was verified the existence of genetic variability between the varieties, allowing the practice of selection. The high estimates of the average heritability suggest significant genetic gains with the practice of selection in the evaluated traits. The methodologies used in the analysis of adaptability and stability were not coincidents in the identification of more productive varieties in the respective maturation segments. The mixed model methodology proved to be more efficient and allowed the identification of the RB92579 variety as the most productive for TSH and TCH and of the RB942520 and RB813804 varieties for PCC and ATR.